1925
DOI: 10.1007/bf01331717
|View full text |Cite
|
Sign up to set email alerts
|

Zum Aufbau der Bandenspektra

Abstract: An der /:[and eines experimentellen Tatsachenmaterials yon 16 gcnauer analysierten Bandenspekfra wird gezeigt~ daft zwlschen der 0szillationsenergie der Kerne einerseits und ihrer Rotationsenergm andererseits enge Beziehungen bestehen~ die auf einen inneren Zusammenhang hindeuten und eine Erweiterung des _~Iolektilmodells verlangen. Diese Beziehungen machen es auch sehr wahrscheinlich, dab im Falle der Intensitgtsanomalie bei den N~-und 0.2-Banden die Linien wechselnder Intensitar zu einer Serie zusammenzufass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1
1

Year Published

1926
1926
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 0 publications
1
19
1
1
Order By: Relevance
“…Roy [5] tried to give an improved vibrational expression compared to Mecke [1]. But as it has been recently confirmed that, since some of the band heads of the system are shifted due to interaction of A 2 P i state with the ground X 2 R + state [28], it would never have been possible to find a perfect expression with minimum obs.-cal.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Roy [5] tried to give an improved vibrational expression compared to Mecke [1]. But as it has been recently confirmed that, since some of the band heads of the system are shifted due to interaction of A 2 P i state with the ground X 2 R + state [28], it would never have been possible to find a perfect expression with minimum obs.-cal.…”
Section: Introductionmentioning
confidence: 96%
“…The blue-green system, B 2 R + -X 2 R + transition, of AlO has been known for over 100 years and extensively studied both experimentally and theoretically [1][2][3][4][5][6][7][8][9][10][11][17][18][19]23,24]. The astrophysical importance of AlO and its aeronomical significance is well known [12][13][14][15][16]21,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If quantum chemical calculations are feasible only for model systems rather than the actual targets of chemical research, then vibrational spectroscopy may be the only tool for obtaining information that provides an insight into bond properties. (3) In the realm of computational chemistry, there is also a need for empirical relationships. They may be used to determine suitable bonding force fields for molecular mechanics utilizing force constant -bond length relationships.…”
Section: Introductionmentioning
confidence: 99%
“…After preliminary work by Kratzer [1], Birge [2], and Mecke [3], Morse [4] was the first to derive an empirical relationship between bond length and bond stretching frequency in 1929 (entry 4, Table 4.1) for diatomic molecules. Badger criticized the Morse relationship as being too limited in its practical application [6].…”
Section: Introductionmentioning
confidence: 99%